Designing a collaborative ecosystem for sustainability transition in the furniture industry: The Opendesk case - Italia, Mattia; Pei, Xue; Migliozzi, Silvana (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Humanity faces a period of changes, leading to a global transition with unpredictable outcomes. Design can play a key role in guiding society to face these challenges, helping the different socio-technical system stakeholders cope with the sustainable transition. The change towards more sustainable economic and social systems requires the design of products and services and new business models and integrated systems that deliver them. This implies shifting from individual company thinking towards coalitions and partnerships like collaborative ecosystems. The furniture industry is facing a sustainable transition, therefore, companies and the market are experimenting with new approaches, including collaborative ecosystems. Because of this, it is important to understand how design can contribute to the definition, creation, and development of a collaborative ecosystem for sustainable transition in the furniture industry. The article adopts the single case study methodology, proposing the analysis of Opendesk, a furniture delocalised network. The research shows how the design mindset has enabled Opendesk to create a collaborative, scalable, and resilient business that values stakeholders in the system and local production. It was possible to address the challenges of building and maintaining a community and network, creating engagement through design. Through the design mindset in the creation of a collaborative ecosystem, it was possible to help local manufacturers to be efficient and economically viable, allowing customers to contribute to the local economy and value. The case study shows the potential of design to catalyse relationships for fruitful collaborations between stakeholders with different goals and provide systemic innovations.